Les dispositifs et les enjeux de la politique familiale au Nouveau-Brunswick - Octave Keutiben (Enfances, Familles, Générations, 2020)
Research Framework: The publication of the New Brunswick Family Plan and the Early Learning and Child Care Action Plan sparked interest in understanding how family issues are considered in New Brunswick public policies. Objectives: This article examines the mechanisms and issues of New Brunswick's family policy. We first describe the New Brunswick Family Plan to underscore family policy provisions. Next, we examine the principles and implications of these provisions for families. Methodology: The study is based on a mixed methodology. On the one hand, a qualitative analysis of documents provides an understanding of the evolution and recent changes in New Brunswick’s family policy. On the other hand, a literature review helps to characterize it and to understand how its new provisions may affect families. Some facts are illustrated with quantitative data. Results: New Brunswick's family policy clearly targets low-income families in order to offset the economic cost of children, encourage work and facilitate work/family reconciliation. The New Brunswick Early Learning Centre designation allows for childcare costs to be controlled and will surely have an impact on families, especially low-income and single-parent families. The low coverage rate of licenced child care will undoubtedly limit this impact. Conclusions: Child care is dominating the current orientation of New Brunswick's family policy. The challenge for the province will be to increase the coverage rate of child care services to contemplate creating a network of higher quality services universally accessible and affordable for all families by 2030. Contribution: By analyzing New Brunswick's family policy, this article contributes to understanding its current mechanisms and its implications for families.